2013
DOI: 10.1371/journal.pone.0059399
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of Viral Infections in Wild Carnivores Reveals Ubiquity of Parvovirus and Susceptibility of Egyptian Mongoose to Feline Panleukopenia Virus

Abstract: The exposure of wild carnivores to viral pathogens, with emphasis on parvovirus (CPV/FPLV), was assessed based on the molecular screening of tissue samples from 128 hunted or accidentally road-killed animals collected in Portugal from 2008 to 2011, including Egyptian mongoose (Herpestes ichneumon, n = 99), red fox (Vulpes vulpes, n = 19), stone marten (Martes foina, n = 3), common genet (Genetta genetta, n = 3) and Eurasian badger (Meles meles, n = 4). A high prevalence of parvovirus DNA (63%) was detected amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 54 publications
5
68
2
Order By: Relevance
“…The possibility that CPV-2 vaccine virus may have also contributed to the clinical disease of the Yorkshire puppy is remote, since vaccine parvovirus was not isolated in cell culture after three passages indicating that, if present, the viral charge was very low, in agreement with the high Ct value (38.5) obtained in the real time PCR. Furthermore, we obtained lower Ct values with fresh samples from cats and dogs with active disease (Duarte et al 2013), in contrast with the high Ct value obtained for the index case. Moreover, previous studies confirmed that most cases of parvovirus-like disease occurring shortly after vaccination were related to infection with either field strains of CPV type 2 (CPV-2) or other viruses, bacteria or parasites, rather than to reversion to virulence of the modified live virus contained in the vaccine.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The possibility that CPV-2 vaccine virus may have also contributed to the clinical disease of the Yorkshire puppy is remote, since vaccine parvovirus was not isolated in cell culture after three passages indicating that, if present, the viral charge was very low, in agreement with the high Ct value (38.5) obtained in the real time PCR. Furthermore, we obtained lower Ct values with fresh samples from cats and dogs with active disease (Duarte et al 2013), in contrast with the high Ct value obtained for the index case. Moreover, previous studies confirmed that most cases of parvovirus-like disease occurring shortly after vaccination were related to infection with either field strains of CPV type 2 (CPV-2) or other viruses, bacteria or parasites, rather than to reversion to virulence of the modified live virus contained in the vaccine.…”
Section: Discussioncontrasting
confidence: 85%
“…The seroprevalence of CAdV-1 in foxes and wolves was highly variable, ranging from 4.7% to 100%. For wild carnivores from Portugal, data is limited to red foxes (n=4), with none testing positive for CAdV-1 (Duarte et al 2013). Wild species are likely reservoirs of CAdV-1, from which sporadic spill over to susceptible unvaccinated domestic dogs may occur.…”
mentioning
confidence: 99%
“…These were the SARS coronavirus (SARS CoV) (Guan et al, 2003;Poon et al, 2005); HPAI H5N1 (Roberton et al, 2006;Wu et al, 2013) and a number of variants of the rabies virus (Enurah et al, 1988a;Wilde et al, 1991;Tremlett et al, 1994;Nel et al, 2005;Susetya et al, 2008;Pfukenyi et al, 2009;Matsumoto et al, 2011). Three important viruses of domestic carnivores were also reported, including canine distemper virus (CDV) (Machida et al, 1992;Hur et al, 1999;Chandra et al, 2000;L opez-Peña et al, 2001;Hirama et al, 2004;Chen et al, 2007;Takayama et al, 2009), feline parvovirus (caused by the feline panleukopenia virus, FPV) (Ikeda et al, 1999;Demeter et al, 2009) and canine parvovirus (CP) (Santos et al, 2009;Xiao-Ying et al, 2011;Duarte et al, 2013). In more recent years, the use of advanced molecular techniques has enabled the identification of five novel viruses of uncertain significance.…”
Section: Resultsmentioning
confidence: 99%
“…Neurological signs Tanzania (wild) (Marston et al, 2012) Family Paramyxoviridae Canine distemper virus M Binturong (Arctictis binturong), Masked palm civet, Common palm civet (Paradoxurus hermaphroditus), Small Indian civet, Common genet Depression, dyspnoea, coughing, oculonasal discharge, gastrointestinal signs, dehydration, neurological signs, foot pad hyperkeratosis USA, Korea, Taiwan, Japan, Spain, Thailand (wild, farm, zoo) (Machida et al, 1992;Hur et al, 1999;Chandra et al, 2000;L opez-Peña et al, 2001;Hirama et al, 2004;Chen et al, 2007;Takayama et al, 2009;Techangamsuwan et al, 2014) Family Parvoviridae Feline panleukopenia virus M Formosan gem-faced civet (P. larvata taivana), Common palm civet Lethargy, vomiting, diarrhoea Taiwan, Hungary (farm, zoo) (Ikeda et al, 1999;Demeter et al, 2009) Canine parvovirus M Common genet, Masked palm civet Fever, diarrhoea, depression, anorexia, vomiting Portugal, China (wild) (Santos et al, 2009;Xiao-Ying et al, 2011;Duarte et al, 2013) Family Reoviridae Mammalian reovirus MPC/04…”
Section: African Civetmentioning
confidence: 99%
“…The very high prevalence of CPV-2a/2b infections in these large cats compared to domestic cats may suggest a higher susceptibility of these species for these virus types . An isolate from a stone marten (Martes foina) collected in Portugal revealed the presence of CPV-2b (Duarte et al, 2013), such a stone marten CPV-2a strain was referred by Steinel et al (2001). In Italy, four isolates from wolves analysed by Battilani et al (2001) were antigenically and genetically identified as CPV-2b.…”
Section: Wild Animalsmentioning
confidence: 99%